Japońskie animacje a folklor w narracjach o tożsamości narodowej - BOCHNIARZ, MAREK; YOSHIDA, IZUMI (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
This paper studies the activity of Japanese directors who decided to make film adaptations of the Momotaro story, a classic legend based on Japanese folklore and the most popular one in the modern period. This activity is studied within the framework of cultural politics. The works examined belong to the early period of Japanese animation and war propaganda films, as well as studio-based anime productions which were made in the postwar period.